Cultures d’action et modes partagés d’organisation des constructions de sens - Jean-Marie Barbier (Revue d'anthropologie des connaissances)
Drawing on the one hand, on a number of attempts to apprehend the issue of frames of mind for action, and on the other hand, on the empirical analysis of professional thinking in the field of educational interventions, the author endeavors to construct the concept of “cultures of action”, defined as a shared mode of organization in sense-making focused on activities. Running across the various forms of action, this concept, in comparison to the various tools it draws inspiration from, allows us to bind together the individual and collective dimensions, the stable and changing dimensions, and the mental, affective, conative and discursive elements of action. It strives to highlight the fact that frames of mind are both *familiar to* and *absent from* thought as such. It is part of a larger project aiming to create tools designed to apprehend the joint construction of activities and of individual subjects - and collectives thereof - within the scope of (inter)activities.